Pembentukan Kelompok Sadar Wisata Pada Desa Cipaganti Garut Jawa Barat - Untung Novianto; Arsya Arba (JURPIKAT, 2026)
This community service activity aims to form a Tourism Awareness Group as a forum for organizing the community in managing the potential of coffee agrotourism in Cipaganti Village, Garut Regency, West Java. This village has superior potential in the form of Arabica coffee and Ateng coffee which have not been managed optimally due to the absence of community-based tourism institutions. The approach used is Participatory Action Research PAR which emphasizes active community participation in every stage of the activity from identifying planning problems to evaluation. The expected result is the formation of Pokdarwis which functions as a driver of the local economy, increasing community capacity in tourism management and increasing the added value of coffee products through tourism-based processing and marketing. The findings of the activity show that strengthening community-based institutions is able to increase collective awareness of the community in managing village potential and opening up new economic opportunities based on sustainable tourism.